Penentuan Tingkat Return Saham Dilihat Dari Laba dan Arus Kas Pada Perusahaan Pertambangan Batu Bara di Indonesia - Seflidiana Roza; Nurhayati Nurhayati; Mita Anggraini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to examine the partial and simultaneous effects of net profit and cash flow on stock returns in coal mining subsector companies listed on the Indonesia Stock Exchange between 2021 and 2024. Purposive sampling was used to choose a sample of 25 companies from the 34 enterprises that made up the research population. Secondary data from the company's annual financial statements over a four-year period is used in this study as quantitative data. Multiple linear regression analysis, the determination coefficient (R2) test, and hypothesis testing using the t-test and F test were among the analytical methods employed. The equation Y = 14.410 + 7.997 × 10⁻¹¹ X1 − 9.904 × 10⁻¹¹ X2 + e was revealed by regression analysis. The first hypothesis was rejected since the t-test revealed that net profit had no significant impact on stock returns, with a tcal value of 1.560 < ttable 2.006 and a significance of 0.125 > 0.05. On the other hand, the second hypothesis is accepted since cash flow has a considerable impact on stock returns, with a value of |tcal| 2.054 > table 2.006 and significance 0.045 < 0.05. Nevertheless, with a score of Fcal 2.109 < Ftable 3.175 and a significance of 0.132 > 0.05, the F test results demonstrate that net profit and cash flow do not concurrently have a significant impact on stock returns. Only 7.5% of the variation in stock returns can be explained by the independent variable, with additional factors outside the study model influencing the remaining portion, according to a determination coefficient value (R²) of 0.075.